2018
DOI: 10.1212/nxg.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

Increased KCNJ18 promoter activity as a mechanism in atypical normokalemic periodic paralysis

Abstract: ObjectiveTo identify the genetic basis of a patient with symptoms of normokalemic sporadic periodic paralysis (PP) and to study the effect of KCNJ18 mutations.MethodsA candidate gene approach was used to identify causative gene mutations, using Sanger sequencing. KCNJ18 promoter activity was analyzed in transfected HEK293 cells with a luciferase assay, and functional analysis of Kir2.6 channels was performed with the two-electrode voltage-clamp technique.ResultsAlthough we did not identify harmful mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(29 reference statements)
0
8
0
1
Order By: Relevance
“…The Kir channel family is encoded by KCNJ genes [9]. The KCNJ18 gene encodes Kir 2.6, which is one of the seven Kir subfamilies [1][2][9][10]. KCNJ18-related mutations have been found in up to 33% of the thyrotoxic patients with periodic paralysis [3,11].…”
Section: Discussionmentioning
confidence: 99%
“…The Kir channel family is encoded by KCNJ genes [9]. The KCNJ18 gene encodes Kir 2.6, which is one of the seven Kir subfamilies [1][2][9][10]. KCNJ18-related mutations have been found in up to 33% of the thyrotoxic patients with periodic paralysis [3,11].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, this channel was considered so far as a less likely candidate for paralysis and was no target candidate in well-established screening panels (see Kuhn and colleague [6]). The study and results were reported recently elsewhere in Soufi and colleagues [7]. Note that without the doctor's hint to consider ion channels, the patient would never have conducted these experiments.…”
Section: Statistic Work…mentioning
confidence: 83%
“…Ihm wurde eine kaliumarme, eher natriumreiche Kost empfohlen sowie den Kaliumspiegel senkende Medikamente. Fortan waren die immer wiederkehrenden Lähmungsattacken verschwunden [ 41 ]. Im Nachgang zu der Sendung gab es zahlreiche Anfragen von Menschen mit ähnlichen Symptomen, die an heimatnahe Zentren für seltene Erkrankungen vermittelt werden konnten [ 42 ].…”
Section: Seltene Erkrankungen Bekannt Gemacht Durch Dr Von Hirschhauunclassified